Effect of Unemployment, Inflation and Foreign Direct Investment on Economic Growth in Sub-Saharan Africa - Correa, Ebou (Universitas Airlangga, 2023)
This research explores the influence of unemployment, inflation and FDI on GDP growth from 1991 - 2021. To estimate the model's short-run and long-run phases, the ARDL model was utilized. The Granger causality test, the Error Correction Model (ECM) approach, and the cointegration test were all applied during the investigation. GDP growth, FDI, unemployment, and inflation are among the variables considered. According to the results of the stationarity test, GDP growth and inflation (INF) were stationary at the level, whereas unemployment and FDI were stationary at the first difference. The cointegration test results demonstrated that the variables under consideration had a long-run association. The ECM outcomes also found that, while unemployment and inflation have negative effects on GDP growth, FDI has a positive effect. Finally, the Granger causation analyses showed that none of the variable granger cause the other. The finding suggests that the government should implement policies that manage unemployment and inflation while also encouraging FDI inflows to improve GDP growth.